Prospective Analysis of Distribution Network Reconstruction on Electric Vehicles access to Demonstration District - Yujun, Liu; Qingshan, Xu; Kai, Chen; Xiaohui, Xu (Elektronika ir Elektrotechnika, 2013)
With the accelerated pace of plug-in electric vehicles (EV) access to the smart grid, large quantities of EV charged in old communities may cause the overload of distribution network. Reconstruction of the network appropriately and accordingly should be a fundamental solution to prevent the potential crisis. In this paper, prospective scale of EV is firstly estimated with the statistics of historical ownership of vehicles through logistic curve based on least absolute deviation (LAD) method. Under the scenarios estimated, the Monte Carlo simulation method is applied to determine the starting state of charge (SOC) and the initial point. Then an assumed demonstration district is employed to study the charging load in the uncoordinated charging mode at different EV penetration level. Simulation results indicate that, in the future, EV will pose great pressure on the distribution network and the reconstruction of power facilities such as transformers and transmission lines is necessary to ensure the security and stability of the network. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.4554